The Effectiveness of Zeep Quiz Interactive Learning Media in Improving Students’ Cultural and Civic Literacy in Pancasila Education: A Quasi-Experimental Study - Ahmad Fakih; Muhammad Khalid Faruq (Journal of Educational Sciences, 2026)
Cultural and civic literacy is important for enabling students to understand cultural diversity, national values, citizens’ rights and responsibilities, and tolerance. This study aimed to examine the effectiveness of Zeep Quiz as an interactive learning medium for improving cultural and civic literacy in Pancasila Education. A quantitative quasi-experimental method with a pretest-posttest nonequivalent control group design was employed. The sample consisted of 32 fifth-grade students selected through purposive sampling, with 16 students in each group. Data were collected using a 15-item multiple-choice test covering four aspects of cultural and civic literacy. The instrument was reviewed by experts for content suitability and alignment with the research objectives. Data were analyzed using descriptive statistics, the Shapiro-Wilk test, Levene’s test, paired-samples t-test, independent-samples t-test, and N-Gain analysis. The experimental group’s mean score increased from 68.94 to 85.13, while the control group increased from 68.19 to 74.13. The N-Gain was moderate for the experimental group (0.554) and low for the control group (0.191). The independent-samples t-test indicated a significant difference between posttest scores. These findings suggest that Zeep Quiz-supported learning can provide a more interactive learning experience and contribute to the development of students’ cultural and civic literacy.